COVID-19 lockdown impact on the physical activity of adults with progressive muscle diseases. Issue 1 (18th March 2021) - Roberts-Lewis, Sarah F; Ashworth, Mark; White, Claire M; Rose, Michael R
Abstract : Introduction: This short article summarises findings about reduced physical activity of adults with progressive muscle disease as a result of COVID-19 lockdown. Methods: As part of an ongoing longitudinal cohort study, we prospectively and objectively measured physical activity using accelerometry at baseline in 2019 and follow-up in 2020. A subset of 85 participants incidentally had follow-up data collected during the first UK COVID-19 lockdown from 23 March to 4 July 2020. Thus, for this cohort we had activity data from before and during the COVID-19 pandemic and we were able to prospectively and accurately quantify the changes in their physical activity. Results: Our data highlighted reduced overall activity intensity and reduced light activity time in particular. Conclusions: From our findings, we can infer specific evidence-based recommendations about how to redress inactivity secondary to COVID-19 restrictions for adults with progressive muscle diseases. These recommendations are likely to be generalisable to other groups who are vulnerable to functional decline secondary to prolonged inactivity.